Exploring the Relation between Realised Volatility and Trading Volume: Evidence from International Stock Market - Samuel Tabot Enow (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Objective: The sequential information theory and mixed distribution hypothesis contends that there exists a bi-directional relation between realised volatility and trading volume. This position has led to the proposition that new information spreads sequentially and reaches market participants at varying times. The purpose of this study was to re-examine these theories. Research Design & Methods: A Granger causality test, Mean Square Error and Mean Average error models were applied to investigate the relationship between realised volatility and trading volume for a sample of five international stock markets from March 5, 2018, to March 5, 2023. Findings: The findings of this study contradict the proposition put forth by the sequential information theory and mixed distribution hypothesis where no meaningful relationship was observed between realised volatility and trading volume except for the CAC 40. Hence, new information rather filters through financial markets at the same time. This finding maybe the explanation for the ever-increasing financial contagion between financial markets. Contribution & Value Added: Traders may need to rely on other indicators and adjust their strategies to incorporate different signals or factors that are more relevant for predicting or identifying market movements. It may become more challenging to gauge the liquidity conditions in the market based solely on volatility. Market participants may need to rely on other liquidity indicators, such as bid-ask spreads, order book depth, or trade size distribution, to assess market liquidity.